A method for preparing a multistage nano-porous RuAl / Ru heterojunction electrocatalyst electrode sheet for lithium-carbon dioxide battery anodes

CN117096361BActive Publication Date: 2026-10-30UNIV OF JINAN
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311104250.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-30
Publication Date
2026-10-30
Estimated Expiration
2043-08-30

AI Technical Summary

Technical Problem

然而,金属钌自然丰度较低、价格昂贵,且钌基纳米电催化剂通常需要以金属盐作为前驱体,利用传统的浸渍法、水热法、溶剂热法以及溶胶凝胶法等进行制备

Benefits of technology

[0010]本发明的优点:采用简便温和的自由腐蚀方法制备高质量的多级纳米多孔RuAl/Ru异质结电催化剂,制备方法重复性好、简便温和绿色、成本低廉,制得的催化剂结构均匀,可重复性高,适合规模化制备。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117096361B_ABST
    Figure CN117096361B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a multistage nano-porous RuAl / Ru heterojunction electrocatalyst sheet for a lithium-carbon dioxide battery positive electrode, and a RuAl / Ru heterojunction electrocatalyst with a three-peak nano-porous structure and abundant heterojunction interfaces is prepared through a dealloying technology. In the multistage nano-porous RuAl / Ru heterojunction electrocatalyst, the introduction of Al with a lower electronegativity deeply changes the chemical micro-environment of Ru, such as atomic arrangement, coordination environment and bonding mode, and endows the RuAl intermetallic compound with unique geometric structure and electronic structure; the RuAl intermetallic compound further forms abundant heterojunction interfaces with Ru, further promotes the electronic redistribution in the multistage nano-porous RuAl / Ru heterojunction electrocatalyst, and thus significantly improves the intrinsic activity of the catalyst; the open three-dimensional multistage porous metal skeleton structure can provide channels for CO2 diffusion and electrolyte infiltration, provide space for discharge product deposition, be beneficial to efficient electron transmission, and be beneficial to sufficient exposure of active sites, so that sufficient heterogeneous reaction interfaces required by CO2 reduction and discharge reaction can be obtained, and the reversibility and kinetics of the lithium-carbon dioxide battery reaction are significantly improved; the preparation method of the multistage nano-porous RuAl / Ru heterojunction electrocatalyst sheet is simple, green, safe and good in repeatability, and can realize large-scale preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrocatalytic materials, specifically to a method for preparing a multi-level nanoporous RuAl / Ru heterojunction electrocatalyst electrode for lithium-carbon dioxide battery cathodes. Background Technology

[0002] Rechargeable lithium-carbon dioxide batteries use CO2 as the working medium to achieve electrochemical energy conversion and storage, boasting a theoretical energy density as high as 1876 Wh / kg, making them a promising green energy storage device. However, the slow kinetics of CO2 reduction and evolution reactions in lithium-carbon dioxide batteries often lead to problems such as large charge-discharge polarization, low energy efficiency, poor rate performance, and poor cycle performance, limiting their practical applications. Therefore, developing high-performance cathode catalysts to improve the kinetics of CO2 reduction and evolution reactions is crucial for advancing the development of lithium-carbon dioxide batteries.

[0003] In recent years, researchers have discovered that ruthenium exhibits good intrinsic catalytic activity for CO2 reduction and evolution reactions in lithium-carbon dioxide batteries. However, metallic ruthenium has low natural abundance and is expensive, and ruthenium-based nanocatalysts typically require metal salts as precursors and are prepared using traditional methods such as impregnation, hydrothermal, solvothermal, and sol-gel methods. These preparation methods are usually complex, require harsh conditions such as high temperatures, have low yields, are difficult to control in terms of composition, pollute the environment, have long production cycles, and are affected by many factors, making them unsuitable for practical production applications. Summary of the Invention

[0004] To address the problems existing in the prior art, this invention aims to provide a method for preparing a hierarchical nanoporous RuAl / Ru heterojunction electrocatalyst electrode for lithium-carbon dioxide battery cathodes. The preparation process is simple, reproducible, and exhibits excellent performance as a lithium-carbon dioxide battery cathode electrocatalyst. The RuAl / Ru heterojunction electrocatalyst prepared using dealloying technology possesses abundant porous channels, a large specific surface area, and an ordered lattice structure of the RuAl intermetallic compound formed by the introduction of inexpensive, low-electron-negativity Al into Ru, along with abundant interfaces between the Ru and Al. This significantly improves catalytic activity while reducing the amount of Ru required, thereby enhancing the performance of lithium-carbon dioxide batteries.

[0005] The present invention involves preparing a multi-level nanoporous RuAl / Ru heterojunction electrocatalyst electrode by free etching of a RuAl matrix alloy in a dilute acid or dilute alkali aqueous solution. The multi-level nanoporous RuAl / Ru heterojunction electrocatalyst consists of a sponge-like framework of intermetallic compounds RuAl and Ru intersecting each other at multiple dimensions. Using this multi-level nanoporous RuAl / Ru heterojunction electrocatalyst as the positive electrode catalyst, polytetrafluoroethylene as a binder, and Ketjen carbon as a conductive agent, the positive electrode sheet is assembled into a lithium-carbon dioxide battery. The battery operates at 200 mA g. -1 At current density, the battery can stably cycle more than 120 times, and the charge / discharge voltage polarization can be kept stable below 1.3 V, demonstrating good cycle performance and stability.

[0006] As a preferred technical solution, the preparation of the multi-level nanoporous RuAl / Ru heterojunction electrocatalyst specifically includes the following steps: (1) High-purity ruthenium and aluminum are melted in a vacuum arc furnace or a high-frequency induction furnace to obtain RuAl matrix alloy ingots. The atomic percentage of Ru in the RuAl matrix alloy ingots is 0.1-50% and the atomic percentage of Al is 50-99.9%. (2) The RuAl matrix alloy ingot obtained in step (1) is polished with sandpaper to remove the oxide layer on the surface. The molten liquid alloy is rapidly solidified on a copper roller rotating at a high speed of 900 to 5000 r / min through a single roller quenching system to obtain RuAl matrix alloy strips with a thickness of 0.1 to 300 micrometers, a width of 0.1 to 5 cm, and a length of 0.1 to 60 cm. (3) The RuAl matrix alloy strips obtained in step (2) are immersed in dilute acid or dilute alkali aqueous solution for free corrosion. The corrosion temperature range is 20~60 ℃ and the corrosion time is 1-100 h. The product is washed with ultrapure water multiple times until the washing liquid is neutral. The product is then vacuum dried to obtain a multi-level nanoporous RuAl / Ru heterojunction electrocatalyst.

[0007] As a preferred technical solution, the multi-level nanoporous RuAl / Ru heterojunction electrocatalyst comprises two phases, RuAl and Ru, with the Ru phase accounting for 50-95% of the total mass and the RuAl phase accounting for 5-50% of the total mass. The pore wall size of the nanoporous RuAl / Ru heterojunction electrocatalyst is 1-300 nm, the primary pore size is 50-300 nm, the secondary pore size is 2-50 nm, and the tertiary pore size is 0.1-5 nm.

[0008] As a preferred technical solution, the dilute acid aqueous solution is hydrochloric acid or sulfuric acid aqueous solution with a concentration range of 0.01~2 mol / L; the dilute alkali aqueous solution is sodium hydroxide or potassium hydroxide aqueous solution with a concentration range of 0.05-2 mol / L.

[0009] As a preferred technical solution, the multi-level nanoporous RuAl / Ru heterojunction electrocatalyst electrode for lithium-carbon dioxide battery cathode has a RuAl / Ru heterojunction electrocatalyst mass fraction of 20% to 60%, a Ketjen carbon mass fraction of 20% to 60%, and a polytetrafluoroethylene mass fraction of 5% to 30%.

[0010] Advantages of this invention: High-quality multi-level nanoporous RuAl / Ru heterojunction electrocatalysts are prepared using a simple and mild free corrosion method. The preparation method has good reproducibility, is simple, mild, green, and low cost. The obtained catalyst has a uniform structure, high reproducibility, and is suitable for large-scale preparation.

[0011] The interconnected three-dimensional multi-scale sponge-like framework structure of the hierarchical nanoporous RuAl / Ru heterojunction electrocatalyst is conducive to electron conduction and mass transport; the open multi-scale pore structure is conducive to high-efficiency mass transfer and containment of discharge products; the large specific surface area is conducive to the exposure of active sites, so as to form a rich multiphase interface required for CO2 reduction and precipitation reactions.

[0012] In hierarchical nanoporous RuAl / Ru heterojunction electrocatalysts, the heterostructure of RuAl intermetallic compounds intersecting with Ru can form abundant nanoheterointerfaces, inducing interfacial electron redistribution and producing significant electronic structure effects. This increases both the number of catalytic sites and their activity. When lithium-carbon dioxide batteries are assembled with electrodes made of hierarchical nanoporous RuAl / Ru heterojunction electrocatalysts, the activity at 200 mA g... -1 At the current density, the battery can stably cycle more than 120 times, and the charge / discharge voltage polarization can be stabilized below 1.3 V, which significantly improves the catalytic activity of the electrocatalyst for CO2 reduction and evolution reactions in lithium-carbon dioxide batteries.

[0013] The preparation method has excellent versatility, and the composition and pore structure of the porous alloy are adjustable and controllable. Attached Figure Description

[0014] Figure 1 X-ray diffraction pattern of the hierarchical nanoporous RuAl / Ru heterojunction electrocatalyst prepared in Example 1; Figure 2 Scanning electron microscope (SEM) images, transmission electron microscope (TEM) images, and elemental distribution images of the hierarchical nanoporous RuAl / Ru heterojunction electrocatalyst prepared in Example 1; Figure 3 Nitrogen adsorption-desorption curves and DFT and BJH pore size distribution curves of the multi-level nanoporous RuAl / Ru heterojunction electrocatalyst prepared in Example 1; Figure 4 The energy dispersive spectrum of the multi-level nanoporous RuAl / Ru heterojunction electrocatalyst prepared in Example 1; Figure 5 The multi-level nanoporous RuAl / Ru heterojunction electrocatalyst electrode prepared in Example 1 was subjected to a reaction at 200 mA g. -1 Evolution curves of charge / discharge termination voltage of lithium-carbon dioxide batteries obtained by DC charge / discharge tests at current density. Figure 6 The multi-level nanoporous RuAl / Ru heterojunction electrocatalyst electrode prepared in Example 1 was subjected to a reaction at 200 mA g. -1 Time-voltage curves of lithium-carbon dioxide batteries obtained by DC charge-discharge tests at current density. Figure 7 The rate performance of the lithium-carbon dioxide battery was obtained by performing DC charge-discharge tests on the multi-level nanoporous RuAl / Ru heterojunction electrocatalyst electrode prepared in Example 1 at different current densities. Detailed Implementation

[0015] The present invention will be further described below with reference to embodiments. The described embodiments and their results are for illustrative purposes only and should not, and will not, limit the invention as described in detail in the claims. Example 1

[0016] A method for preparing a hierarchical nanoporous RuAl / Ru heterojunction electrocatalyst electrode for lithium-carbon dioxide battery cathode, the specific steps of which are as follows: A positive electrode sheet was prepared by using 45% RuAl / Ru heterojunction electrocatalyst as the positive electrode catalyst, 45% Ketjen carbon as the conductive agent, and 10% polytetrafluoroethylene as the binder to assemble a lithium-carbon dioxide battery.

[0017] The preparation of the multi-level nanoporous RuAl / Ru heterojunction electrocatalyst specifically includes the following steps: (1) High-purity ruthenium and aluminum are smelted in a vacuum arc furnace or a high-frequency induction furnace to obtain Ru5Al. 95 Parent alloy ingot.

[0018] (2) The Ru5Al obtained in step (1) 95The base alloy ingot was polished with sandpaper to remove the surface oxide layer. The molten liquid alloy was then rapidly solidified on a copper roller rotating at a high speed of 2500 r / min using a single-roller quenching system, resulting in Ru5Al with a thickness of approximately 100 micrometers, a width of approximately 0.3 cm, and a length of approximately 10 cm. 95 Parent alloy strip.

[0019] (3) The Ru5Al obtained in step (2) 95 The parent alloy strip was immersed in a 0.1 mol / L hydrochloric acid aqueous solution for free corrosion at a temperature of 27 °C for 12 h. The product was washed multiple times with ultrapure water until the washing solution was neutral, and then vacuum dried to obtain a multi-level nanoporous RuAl / Ru heterojunction electrocatalyst.

[0020] (4) such as Figure 1 As shown in the X-ray diffraction pattern, the hierarchical nanoporous RuAl / Ru heterojunction electrocatalyst is composed of two phases: Ru (JCPDS #06-0663) and RuAl (JCPDS #29-1404).

[0021] (5) such as Figure 2 Scanning electron microscope images, transmission electron microscope images, and elemental distribution maps and Figure 3 As shown in the nitrogen adsorption-desorption curves and DFT and BJH pore size distribution curves, the hierarchical nanoporous RuAl / Ru heterojunction electrocatalyst has a primary pore size of approximately 100 nm, a secondary pore size of approximately 20 nm, and a tertiary pore size of approximately 3 nm. The specific surface area of ​​the hierarchical nanoporous RuAl / Ru heterojunction electrocatalyst is 39.8 m². 2 g −1 Furthermore, ruthenium and aluminum are evenly distributed.

[0022] (6) For example Figure 4 As shown in the energy dispersive spectroscopy (EDS) spectrum, the atomic percentage of Ru in the hierarchical nanoporous RuAl / Ru heterojunction electrocatalyst is 80.63%, and the atomic percentage of Al is 19.37%. Therefore, the molar percentage of the Ru phase is calculated to be 75.9%, and the molar percentage of the RuAl phase is 24.1%.

[0023] (7) For example Figure 5 at 200 mA g -1 Evolution curves of charge / discharge termination voltage of lithium-carbon dioxide batteries at current density and Figure 6 at 200 mA g -1The time-voltage curve of the lithium-carbon dioxide battery obtained by DC charge-discharge test under current density is shown in the figure. The lithium-carbon dioxide battery assembled with the multi-level nanoporous RuAl / Ru heterojunction electrocatalyst electrode can stably cycle continuously for 140 cycles, or 1400 hours, and the charge-discharge voltage polarization is stable at about 1.25 V.

[0024] (8) such as Figure 7 The rate performance of the lithium-carbon dioxide battery was obtained by DC charge-discharge testing at different current densities, as shown in the graph. The lithium-carbon dioxide battery assembled with the multi-level nanoporous RuAl / Ru heterojunction electrocatalyst electrode exhibits good rate performance at current densities from 0.2 A g / L. -1 Increase to 2 Ag -1 At that time, the charging termination voltage increased only from 3.94 V to 4.20 V, the discharging termination voltage decreased only from 2.79 V to 2.67 V, and the current density decreased from 2 A g. -1 Reduce back to 0.2 A g -1 At that time, the charging termination voltage and discharging termination voltage recovered well to the initial value of 0.2 A g. -1 The test results indicate that the battery has good rate performance.

[0025] This invention provides a method for preparing a multi-level nanoporous RuAl / Ru heterojunction electrocatalyst electrode for lithium-carbon dioxide battery cathodes. By using dealloying technology to selectively and controllably etch away part of the aluminum, a nanoporous RuAl / Ru heterojunction electrocatalyst electrode with a multi-level three-dimensional porous structure is obtained. It exhibits superior catalytic performance for lithium-carbon dioxide battery reactions, and the preparation process is simple, green, and safe, while realizing the resource utilization of CO2 and electrochemical energy conversion and storage.

[0026] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claims. The scope of protection of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a hierarchical nanoporous RuAl / Ru heterojunction electrocatalyst electrode for lithium-carbon dioxide battery cathode, characterized in that: A hierarchical nanoporous RuAl / Ru heterojunction electrocatalyst was prepared by free corrosion of the RuAl matrix alloy in dilute acid or dilute alkali aqueous solution. The hierarchical nanoporous RuAl / Ru heterojunction electrocatalyst consists of a sponge-like framework of intermetallic compounds RuAl and Ru intersecting each other at multiple levels. Using the hierarchical nanoporous RuAl / Ru heterojunction electrocatalyst as the positive electrode catalyst, polytetrafluoroethylene (PTFE) as the binder, and Ketjen carbon as the conductive agent, a positive electrode sheet was fabricated and assembled into a lithium-carbon dioxide battery. The battery was then tested at 200 mA g. -1 At current density, the battery can stably cycle more than 120 times, and the charge / discharge voltage polarization can be kept stable below 1.3 V, demonstrating good cycle performance and stability.

2. The method for preparing a hierarchical nanoporous RuAl / Ru heterojunction electrocatalyst electrode for a lithium-carbon dioxide battery cathode as described in claim 1, characterized in that: The preparation of the multi-level nanoporous RuAl / Ru heterojunction electrocatalyst includes the following steps: (1) High-purity ruthenium and aluminum are melted in a vacuum electric arc furnace or a high-frequency induction furnace to obtain RuAl matrix alloy ingots. The atomic percentage of Ru in the RuAl matrix alloy ingots is 0.1~50%, and the atomic percentage of Al is 50~99.9%. (2) The RuAl matrix alloy ingot obtained in step (1) is polished with sandpaper to remove the oxide layer on the surface. The molten liquid alloy is rapidly solidified on a copper roller rotating at a high speed of 900 to 5000 r / min through a single roller quenching system to obtain RuAl matrix alloy strips with a thickness of 0.1 to 300 micrometers, a width of 0.1 to 5 cm, and a length of 0.1 to 60 cm. (3) The RuAl matrix alloy strips obtained in step (2) are immersed in dilute acid or dilute alkali aqueous solution for free corrosion. The corrosion temperature range is 20 ~ 60 °C and the corrosion time is 1-100 h. The product is washed multiple times with ultrapure water until the washing liquid is neutral. The product is then vacuum dried to obtain a multi-level nanoporous RuAl / Ru heterojunction electrocatalyst.

3. The method for preparing a hierarchical nanoporous RuAl / Ru heterojunction electrocatalyst electrode for a lithium-carbon dioxide battery cathode as described in claim 1, characterized in that: The prepared hierarchical nanoporous RuAl / Ru heterojunction electrocatalyst consists of RuAl intermetallic compound and Ru two phases, with the Ru phase accounting for 50-95% of the total mass and the RuAl phase accounting for 5-50% of the total mass.

4. The method for preparing a hierarchical nanoporous RuAl / Ru heterojunction electrocatalyst electrode for a lithium-carbon dioxide battery cathode as described in claim 1, characterized in that: The multi-level nanoporous RuAl / Ru heterojunction electrocatalyst has a primary pore size of 50 ~ 300 nm, a secondary pore size of 2 ~ 50 nm, and a tertiary pore size of 0.1 ~ 5 nm.

5. The method for preparing a hierarchical nanoporous RuAl / Ru heterojunction electrocatalyst electrode for a lithium-carbon dioxide battery cathode as described in claim 2, characterized in that: In step (3), the dilute acid aqueous solution is hydrochloric acid or sulfuric acid aqueous solution with a concentration range of 0.01 ~ 2 mol / L; the dilute alkali aqueous solution is sodium hydroxide or potassium hydroxide aqueous solution with a concentration range of 0.05-2 mol / L.

6. The method for preparing a hierarchical nanoporous RuAl / Ru heterojunction electrocatalyst electrode for lithium-carbon dioxide battery cathode as described in claim 1, characterized in that: In the multi-level nanoporous RuAl / Ru heterojunction electrocatalyst electrode, the mass fraction of the multi-level nanoporous RuAl / Ru heterojunction electrocatalyst is 20% to 60%, the mass fraction of Ketjen carbon is 20% to 60%, and the mass fraction of polytetrafluoroethylene is 5% to 30%.

Citation Information

Patent Citations

  • Preparation method of nano-porous Ni3Al / Ni heterostructure catalyst for positive electrode of lithium-carbon dioxide battery

    CN115440996A

  • Group i-iii-vi chalcopyrite type thin-film-based solar cell, and its manufacturing method

    JP2009224572A